Thermal analysis and its application to high power GaN HEMT amplifiers - Prejs, A.; Wood, S.; Pengelly, R.; Pribble, W. (2009 IEEE MTT-S International Microwave Symposium Digest, 2009)
A systematic and consistent approach to the thermal modeling and measurement of GaN on SiC HEMT power transistors is described. Since the power density of such multilayered wide bandgap structures and assemblies can be very high compared with other transistor technologies, the application of such an approach to the prediction of operating channel temperatures (and hence product lifetime) is important. Both CW and transient (i.e. pulsed and digitally modulated) thermal resistances are calculated for a range of transistor structures and sizes as a function of power density, pulse length and duty factor and compared with measured channel temperatures and RF parameters. The resulting thermal resistance values have then been imported into new ldquoself-heatingrdquo large signal models so that transistor channel temperatures and the resulting effects on RF performance such as gain, output power and efficiency can be determined during the amplifier design phase. Some practical examples are included in the paper including the temperature rises in the carrier and peaking transistors of a high power Doherty amplifier.